O sistema penal e a garantia dos direitos humanos: os perigos da doutrina do dever de punir na jurisprudência da corte interamericana de direitos humanos - CARDOSO, Emanuela Nazaré Carvalho (2023)
The present research aims to analyze the doctrine of the duty to investigate and punish, built by the Inter-American Court of Human Rights, in the context of the exercise of punitive power and the objective of protecting human rights, using the deductive method of research, through bibliographical research, and jurisprudential survey. To this end, an exposition of the main characteristics of the duty to investigate and punish the violation of human rights imposed on States subject to the Court's jurisdiction will be carried out, in order to analyze its possible consequences in domestic legal systems. Furthermore, it will seek to define the position of the penal system; or as an alternative for the protection of human rights; or as a system that violates these rights, in order to understand the applicability of the doctrine of the duty to investigate and punish. From this, it was concluded that, in the current crisis of the penal system, it is not possible to reconcile the exercise of punitive power with the guarantee of human rights sought by the duty to investigate and punish.